Pachakutik and the rise and decline of the Ecuadorian Indigenous movement - Mijeski, Kenneth J. (Research in international studies. Latin America series, 2011)
The mobilization of militant Indigenous politics is one of the most important stories in Latin American studies today. In this critical work, Kenneth J. Mijeski and Scott H. Beck examine the rise and decline of Ecuador's leading Indigenous party, Pachakutik, as it tried to transform the state into a participative democracy. Using in-depth interviews with political activists, as well as a powerful statistical analysis of election results, the authors show that the political election game failed to advance the causes of Ecuador's poor or the movement's own Indigenous supporters.